Structural transformation of highly active metal–organic framework electrocatalysts during the oxygen evolution reaction - Zhao, Shenlong; Tan, Chunhui; He, Chun-Ting; An, Pengfei; Xie, Feng; Jiang, Shuai; Zhu, Yanfei; Wu, Kuang-Hsu; Zhang, Binwei; Li, Haijing; Zhang, Jing; Chen, Yuan; et al. (Nature energy, 2020)
Metal–organic frameworks (MOFs) are increasingly being investigated as electrocatalysts for the oxygen evolution reaction (OER). Despite their promising catalytic activity, many fundamental questions concerning their structure−performance relationships—especially those regarding the roles of active species—remain to be answered. Here we show the structural transformation of a Ni 0.5 Co 0.5 -MOF-74 during the OER by operando X-ray absorption spectroscopy analysis and high-resolution transmission electron microscopy imaging. We suggest that Ni 0.5 Co 0.5 OOH 0.75 , with abundant oxygen vacancies and high oxidation states, forms in situ and is responsible for the high OER activity observed. The ratio of Ni to Co in the bimetallic centres alters the geometric and electronic structure of as-formed active species and in turn the catalytic activity. Based on our understanding of this system, we fabricate a Ni 0.9 Fe 0.1 -MOF that delivers low overpotentials of 198 mV and 231 mV at 10 mA cm −2 and 20 mA cm −2 , respectively. Metal–organic frameworks (MOFs) are increasingly being explored for electrocatalytic oxygen evolution, which is half of the water splitting reaction. Here the authors show that, under reaction conditions, mixed metal oxyhydroxides form at the nodes of bimetallic MOFs, which are highly catalytically active.